PENGARUH KUALITAS PRODUK, CITRA MEREK DAN PERSEPSI HARGA TERHADAP LOYALITAS PELANGGAN PADA PRODUK KOSMETIK WARDAH - Astuti Atmajayanti; Edy Purwo Saputro (Jurnal Ekonomika: Manajemen, Akuntansi, dan Perbankan Syari'ah, 2024)
The aim of this study is to examine the impact of product quality, brand perception, and price on customer loyalty towards Wardah cosmetic products. This study employed a quantitative approach with one hundred participants. A questionnaire was used in this study's data collection process. This data was obtained directly by researchers through a questionnaire distributed to respondents or students from the Faculty of Economics and Business, Muhammadiyah University of Surakarta who had purchased Wardah cosmetic products. This study used a purposive sampling technique coupled with a non-probability sampling technique. The primary data used in the study came from respondents' responses to closed questionnaires or interviews. Partial Least Square (PLS), aided by SMARTPLS software, is the data analysis method used in this study. The two models used in PLS-SEM analysis are the inner model and the outer model. According to the study's findings, customer loyalty is positively and significantly impacted by product quality. Customer loyalty is significantly and favorably impacted by brand image. Customer loyalty is positively impacted by the way people perceive prices.